If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(8 + 7x) = 36 (8 * -6 + 7x * -6) = 36 (-48 + -42x) = 36 Solving -48 + -42x = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '48' to each side of the equation. -48 + 48 + -42x = 36 + 48 Combine like terms: -48 + 48 = 0 0 + -42x = 36 + 48 -42x = 36 + 48 Combine like terms: 36 + 48 = 84 -42x = 84 Divide each side by '-42'. x = -2 Simplifying x = -2
| 10.00-2.00x=60.00 | | 56=.5*14*h | | 5(y-7)-6=-7(-3y+5)-2y | | 44=50-2(3x+12) | | 2/3x-x=x/15-6/5 | | .285=x+2.05x | | h=56/14 | | (2/52)*(1/51) | | R=6m | | 2x+4+12-8=6*2x | | l-(2+w)=w+5 | | (u^2+3u-28)(6u-18)=0 | | 2/5x-7/20x-2 | | 7x^2-1x-1=0 | | 6r=304 | | 8x+6x+3+9=3x+5+10x | | Y2/3x-4 | | 11v=9v+18 | | -2/3log(5x)-1=-3 | | 2(1x+3)=16 | | c=1/2πt2n | | 13+2(4x-3)=-41 | | v=1/3*12*14 | | (13b-3)-6(2b+2)=-3 | | 2p-5=7p+2p-10 | | v=9*5*2 | | y^2+14y-72= | | 2.5(3j-1)=-8 | | 264=55t | | 35+70x=665 | | x=124-3*x | | y^4-16y=128cosh(2x) |